(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article is devoted to the analysis of the process of transition of Uzbek companies to International Financial Reporting Standards (IFRS), with special attention to the aspect of revaluation of fixed assets in accordance with IAS 16. It examines how changes in accounting standards affect the quality and transparency of financial reporting, which is critical for integration of Uzbek enterprises into the world economy. The work examines both technical and organizational challenges, as well as the opportunities that open up for companies in the light of the transition to IFRS. Particular attention is paid to the need to train and develop professional competencies of employees in the field of IFRS.